2013
DOI: 10.1016/s2221-1691(13)60187-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies on Buchanania lanzan Spreng.-A focus on wound healing with particular reference to anti-biofilm properties

Abstract: From this study it may be concluded that the root extract of B. lanzan revealed significant wound healing potential, which was supported and well correlated with pronounced antibacterial activity of the tested plant parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 39 publications
0
15
0
2
Order By: Relevance
“…Topical application of methanol root extract of B. lanzan (10% (w/w) ointment) significantly (p < 0.05) increased the tensile strength in the incision wound model. B. lanzan also showed significant wound healing activity in excision wound model [28]. However, a study conducted by Chitra et al [29] showed that the methanol fruit extract of B. lanzan did not significantly (p > 0.05) promote wound healing when compared to the control in excision, incision and dead space wound models.…”
Section: Anacardiaceaementioning
confidence: 94%
“…Topical application of methanol root extract of B. lanzan (10% (w/w) ointment) significantly (p < 0.05) increased the tensile strength in the incision wound model. B. lanzan also showed significant wound healing activity in excision wound model [28]. However, a study conducted by Chitra et al [29] showed that the methanol fruit extract of B. lanzan did not significantly (p > 0.05) promote wound healing when compared to the control in excision, incision and dead space wound models.…”
Section: Anacardiaceaementioning
confidence: 94%
“…Từ mẫu thân cây Chay sáng thu hái tại tỉnh Đồng Nai, hai mẫu cao ethyl acetate và n-butanol đã được điều chế. Bốn hợp chất khung phenolic là: protocatechuic methyl ester (1), aloe-emodin (2), naringenin (3), và glucosyringic acid (4) đã được cô lập từ các mẫu này. Cấu trúc hóa học của các hợp chất được xác định bằng phương pháp phổ cộng hưởng từ hạt nhân một chiều và hai chiều, kết hợp so sánh với các tài liệu tham khảo.…”
Section: Tóm Tắtunclassified
“…Thành phần hóa học của loài cùng chi Buchanania lanzan có chứa các hợp chất thuộc khung phenolic như: flavonoid và tannin [2]. Theo y học dân gian thì những loài thuộc chi Buchanania dùng chữa vết thương, trị tiêu chảy, kháng khuẩn, và kháng oxy hóa [1,3].…”
Section: Mở đầUunclassified
See 1 more Smart Citation
“…In our laboratory, studies with the root extract of BL revealed significant antimicrobial activity against different gram positive and gram negative bacteria. In addition the plant extract was also found to display wound healing (topical) properties, and also displayed anti biofilm properties 11 . A number of biofilm producing microorganisms have been found to delay wound healing and the biofilms have been directly implicated in the resistance to commonly used topical antibiotics 12 .…”
Section: Introductionmentioning
confidence: 99%